Candesartan versus imidapril in hypertension: a randomised study to assess effects of anti-AT1 receptor autoantibodies. Issue 6 (4th February 2011) - Wei, Fen; Jia, Xiu-Jie; Yu, Su-Qin; Gu, Ye; Wang, Li; Guo, Xiao-Mei; Wang, Min; Zhu, Feng; Cheng, Xiang; Wei, Yu-Miao; Zhou, Zi-Hua; Fu, Micheal; et al.
Abstract : Background: Anti-angiotensin II receptor subtype 1 (AT1 receptor) autoantibodies have previously been shown in sera of hypertensive patients. This study assessed whether anti-AT1-receptor autoantibody in serum is correlated with the efficacy of an AT1-receptor blocker (ARB; candesartan)-based regimen in hypertensive patients after 8 weeks of treatment. Design: The Study of Optimal Treatment in Hypertensive Patients with Anti-AT1-Receptor Autoantibodies is a multicentre, randomised, blinded endpoint, open-label, parallel-group comparison clinical trial conducted in five centres in Wuhan, China. Treatment is designed as stepwise added-on therapy to reduce blood pressure (BP) <140/90 mm Hg. 512 patients with moderate to severe primary hypertension were randomly assigned to an 8-week treatment with either ARB (candesartan)-based regimen (n=257) or ACE inhibitor (imidapril)-based regimen (n=255). Results: Systolic and diastolic BP was reduced significantly in both treatment groups. The candesartan-based regimen achieved a significantly greater systolic BP reduction than imdapril (30.8±10.3 vs 28.8±10.3 mm Hg, p=0.023). In those anti-AT1 receptor autoantibody-positive hypertensive patients, the mean systolic BP at baseline was higher than in the anti-AT1 receptor autoantibody-negative group (160.5±16.5 vs 156.2±17.7 mm Hg; p=0.006). The mean BP reduction was greater in the candesartan-based regimen than the imidapril-based regimen (−35.4±9.8/16.9±6.9 vs −29.4±9.8/14.2±6.9 mm Hg; p=0.000 and 0.002, respectively), and more patients on imidapril required add-on medications to achieve BP control (94% vs 86%; p=0.03). No correlation was observed between the titre of anti-AT1 receptor autoantibody and the efficacy of candesartan-based therapy. In those anti-AT1 receptor autoantibody-negative patients similar BP lowering was reached in the candesartan and the imidapril-based regimens. Conclusions: An ARB-based regimen is more effective in BP lowering than an ACE inhibitor-based regimen in the presence of anti-AT1 receptor autoantibodies. Trial registration number: This trial has been registered at http://www.register.clinicaltrials.gov/ (identifier: NCT00360763 ).